Communication in The Clinical Routine of Neonatologists - Börner, Nele; Mache, Stefanie; Scutaru, Cristian; Metze, Boris; Bührer, Christoph (Zeitschrift für Geburtshilfe und Neonatologie, 2019)
Introduction Communication is essential to clinical routine, especially in NICUs with their vulnerable patients and the special team caring for them. Communication breakdowns and resulting treatment errors are described in the literature. The aim of this study is to provide an initial quantitative assessment of medical communication in a NICU.Methods For task analysis, 15 Level III-NICU physicians were accompanied for 60 days in early and late shifts; each physician completed the COPSOQ questionnaire. Recorded tasks were assigned to main task categories and subcategories.Results A total of 550 h of main and 100 h of secondary tasks were recorded, on average 9 h daily. The most time-consuming main activity was “Communication” (3 h), followed by “Indirect care/Administration” (2 h) and “Direct patient care” (1.5 h). “Communication” mainly consisted of discussions with colleagues and during early shifts. At 2 min, communication with nursing personnel during rounds was especially low. Communication showed a negative correlation to physician job satisfaction.Discussion This work shows the suspected high proportion of communication in a NICU, especially among physicians themselves. The effectiveness of this communication is not assessable. However, a low proportion of communication with nursing staff is noticeable and reflects the variabiliy in team communication. Improvement of communication is necessary through training on and the application of existing techniques for handoffs and rounds.
Keywords: task analysis; communication; neonatal intensive care unit; handover; multitasking